(3JMUjd Gdege GdcGaj aj Ydej GdYQhV hGdbhGajs - (3CMeO Hf Ydj Hf OGhOs
(3ChdgG (B:s
(3HGSe GdPj eG ef YQhV EdG efg ef LhOg ajgG MhQ JedF s
(3BNQgG (B:s
(3hajg ef CeKGdfG caGjg JeJ GdfSNI GdeHGQcI HMeO Gddg hYhfg s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdYQhV hGdbhGais